Comparative evaluation of diode laser and simvastatin gel in pulpotomy of primary molars: A randomized clinical trial - Madhubala Aripirala; Kalpana Bansal; Vijay Prakash Mathur; Nitesh Tewari; Pooja Gupta; Ajay Logani (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2021)
Background: Pulpotomy is a vital pulp therapy performed in carious pulp exposures in teeth in which the inflamed coronal pulp is removed and medicament is placed to conserve the vital root pulps. Recently, simvastatin which is a cholesterol-lowering drug has been found to be associated with the pulp regenerative potential. Aim: The aim of this parallel two-arm randomized control trial was to evaluate and compare the clinical and radiographic efficacy of diode laser (DL) and simvastatin gel (SG) in pulpotomy of carious primary molars. Methods: Hundred primary molars (in 98 children, 65 males, 33 females with age 4–8 years) requiring pulpotomy were randomized into the DL or SG group. Pulpotomy was performed as per the standardized protocol; thereafter, all teeth were restored with resin modified glass ionomer cement followed by stainless steel crowns. Follow-up evaluations were done at 3 and 12 months using clinical and radiographic criteria. Statistical analysis was done using Chi-square test at a significance level of 0.05. Results: At 12 months, out of 92 teeth available for clinical and radiographic evaluation by blinded evaluators, DL group showed clinical and radiographic success rates of 76.1% and 52.1%, while SG group showed 80.4% and 65.2% success rates, respectively. There was no statistically significant difference between the efficacy of two techniques clinically (P = 0.49) or radiographically (P = 0.30). Conclusions: Both SG and DL had similar efficacy for primary tooth pulpotomy, clinically and radiographically after 12 months. Considering its ease of application and low-cost, SG can be recommended as a potential pulpotomy medicament in primary molars.